Assessment of the Impact of Climate Change on Large Cardamom (Amomum subulatum roxb.) Cultivation in Sankhuwasabha, Nepal - Swar, Prabhat; Timilsina, Umesh; Sah, Ashok; Bohara, Saugat; Shrestha, Able; Chaudhary, Sanjib (International Journal of Applied Sciences and Biotechnology, 2023)
The study was conducted in March, 2021 to assess the impacts of Climate Change on the production of Large Cardamom in Sankhuwasabha district of Nepal. The main purpose of the study was to know the impact of climate change on production of Large Cardamom. Primary data were collected by face to face interaction with 80 farmers with prepared questionnaire. The data were statistically analyzed and processed by using MS-Excel through descriptive and inferential method. The results showed that majority of the respondents were male, janajati, literate and mainly depends upon agriculture occupation as their major source of income. They were familiar about Climate Change scenario revealed that increase in overall temperature, deficit in rainfall during flowering and fruiting has negative impact in crop yield. Occurrence of disease pest like wilt, leaf and root rot, Gabaro, Caterpillar and Chirkey, Furkey has heavily affected Large Cardamom orchard. Secondary data of past 10 year were collected from MoALD, AKC, DHM, World Weather Online etc. Secondary data were analyzed by using regression model and found that average seasonal maximum and minimum temperature was decreased by -0.0137ºC and -0.0045ºC respectively and annual rainfall was increased by 1.2326 mm and productivity decreased by 0.0026 ton/ha annually. Increase in temperature, drought, and lack of better irrigation facility, disease and pest problem, unavailability of quality planting materials were the major constraints faced by the Large Cardamom farmers.Int. J. Appl. Sci. Biotechnol. Vol 11(3): 143-151.